ASSESSING EARLY CHILDHOOD CARIES RISK IN CHILDREN AGED 2-5 YEARS IN CA MAU PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence, select associated risk factors, and assess the risk of early childhood caries among children aged 2-5 years at Huong Duong Kindergarten, Song Doc commune, Ca Mau province in 2024.Materials and methods: A cross-sectional descriptive study was conducted on 246 children aged 2-5 years at Huong Duong Kindergarten. Clinical examinations were performed to record caries indices and assess caries risk based on the Evans R.W protocol (2018).Results: The prevalence of early childhood caries was 90.2%. Caries prevalence increased with age, with significant differences between age groups (p < 0.05). Early childhood caries was significantly associated with the daily consumption of fruit juicesweetened and sweetened beverage consumption (p < 0.05). Caries-risk assessment revealed that 89% of children were at high risk, 8.9% at moderate risk, and 2.1% at low risk.Conclusion: The prevalence of early childhood caries among children aged 2-5 years in Huong Duong Kindergarten is high and associated with certain dietary habits. Most children were classified as having a high risk of caries. Early preventive interventions and improved oral-health awareness from early childhood are needed.
Keywords: Early childhood caries, caries risk assessment, Ca Mau.